India Land Governance Assessment : National Synthesis Report - World Bank (World Bank, Washington, DC, 2016)
As India continues to urbanize and move towards a less agricultural- and more industry-based economy, land demands will continue to grow. Its urban population is expected to increase by more than 200 million by 2030, requiring 4 to 8 million hectares of land for residential use alone. Demands for infrastructure and industry could add a similar amount, summing to total land demand of 5 to10 percent of the land area currently used for agriculture. If not handled well, such massive land use change may increase vulnerability and food insecurity, rent-seeking, environmental problems, social dislocation, inequality, and conflict. But it also provides an opportunity to address the underlying structural issues, propelling India into the league of middle-income countries and laying the ground for significantly advancing shared prosperity and reduced poverty. This synthesis report presents results from land governance self-assessments by six states: The fact that land is a state subject implies that actions to improve land governance need to be initiated at state level. To identify opportunities, six states implemented the Land Governance Assessment Framework (LGAF), a tool that allow comparing the status of their land governance against international good practice along a set of dimensions in a very participatory process. Results are summarized in state reports that were validated publicly and discussed with policy makers in each state. This national report complements these and draws out common areas.